Interactive mobile application for Parkinson's disease deep brain stimulation (MAP DBS): An open-label, multicenter, randomized, controlled clinical trial. (April 2023) - Duffley, Gordon; Szabo, Aniko; Lutz, Barbara J.; Mahoney-Rafferty, Emily C.; Hess, Christopher W.; Ramirez-Zamora, Adolfo; Zeilman, Pamela; Foote, Kelly D.; Chiu, Shannon; Pourfar, Michael H.; Goas Cnp, Clarisse; Wood, Jennifer L.; et al.
Abstract: Introduction: Deep brain stimulation (DBS) is an effective treatment for Parkinson's disease (PD), but its efficacy is tied to DBS programming, which is often time consuming and burdensome for patients, caregivers, and clinicians. Our aim is to test whether the Mobile Application for PD DBS (MAP DBS), a clinical decision support system, can improve programming. Methods: We conducted an open-label, 1:1 randomized, controlled, multicenter clinical trial comparing six months of SOC standard of care (SOC) to six months of MAP DBS-aided programming. We enrolled patients between 30 and 80 years old who received DBS to treat idiopathic PD at six expert centers across the United States. The primary outcome was time spent DBS programming and secondary outcomes measured changes in motor symptoms, caregiver strain and medication requirements. Results: We found a significant reduction in initial visit time (SOC: 43.8 ± 28.9 min n = 37, MAP DBS: 27.4 ± 13.0 min n = 35, p = 0.001). We did not find a significant difference in total programming time between the groups over the 6-month study duration. MAP DBS-aided patients experienced a significantly larger reduction in UPDRS III on-medication scores (−7.0 ± 7.9) compared to SOC (−2.7 ± 6.9, p = 0.01) at six months. Conclusion: MAP DBS was well tolerated and improves key aspects of DBS programming time and clinical efficacy. Highlights: This study is the first to evaluate model-based DBS programming in a randomized controlled clinical trial. This study shows the utility of the MAP DBS platform with multiple anatomical targets, DBS systems, and clinical workflows. The results suggest the utility of MAP DBS in the programming process, and will be further explored to develop new clinical practices that reduce the burden of therapy optimization.